Morphological and phylogenetic studies of Agaricus bresadolanus, Agaricus infidus (nom. inval.) and Agaricus romagnesii (Agaricaceae) reveal their conspecificity and variation in toxicity of this taxon - Parra, L.a.; Vizzini, A.; Ercole, E.; Geml, J. (Phytotaxa, 2023)
Original morphological descriptions and newly generated ribosomal DNA sequence data of A. bresadolanus, “A. infidus” and A. romagnesii are compared in this manuscript. In 23 specimens we evaluated the main morphological characters traditionally used to distinguish these taxa: shape of the stipe base, odour, size and shape of spores, presence/absence of cheilocystidia, and toxicity. The ITS rDNA region was sequenced in all specimens, except for an authentic collection of A. romagnesii (KW-M 71176) and two specimens with subglobose spores attributed to “A. infidus” (as A. alessii nom. inval.) by Curreli & Contu. No diagnostic molecular characters were found among all specimens examined that would justify the separation of the originally described entities A. bresadolanus, “A. infidus” and A. romagnesii. Based on our analysis of the morphological and molecular characters, we conclude that all three entities belong to a single taxon, whose correct name is A. bresadolanus based on priority over A. romagnesii. The apparent contradiction between the ellipsoid spores found by us in the two specimens of “A. infidus” identified by Alessio and the subglobose spores depicted by him in the original publication is explained by the extreme variability of the spore shape in this taxon. Our morphological study of the two specimens identified as “A. alessii” suggests that they might belong to A. pseudopratensis a member of A. sect. Xanthodermatei or to an unknown taxon. Nomenclatural problems of the names “A. infidus”, “A. alessii” and A. bresadolanus are revisited and it is concluded that the two first names are invalidly published.